Acyclic cucurbit[n]uril conjugated dextran for drug encapsulation and bioimaging. Issue 62 (20th July 2017) - Chen, Jiafu; Liu, Yamin; Mao, Dake; Ma, Da
Abstract : Acyclic CB[ n ] conjugated dextran for drug encapsulation and bioimaging. Abstract : An acyclic cucurbit[ n ]uril (CB[ n ]) conjugated dextran is developed as a new biomaterial for drug delivery and bioimaging. This biomaterial retains the host–guest recognition properties of acyclic CB[ n ]s. It is able to directly encapsulate anti-tumor drugs 5-fluorouracil and temozolomide. This polymeric material can form a supramolecular assembly with polyethyleneimine (PEI). Although there is no conventional chromophore in these supramolecular systems, they exhibit aggregation-induced emission (AIE) in water with a quantum yield of 10%. This supramolecular assembly is used for bioimaging in vitro with good biocompatibility.